Diagnostics of Psychological Well-Being of Primary School Children in Full-Time and Family Education - Lubovsky D.V.; Milova N.S. (Психолого-педагогические исследования, 2021)
The study is focused on the comparative assessment of elementary school children psychological well-being in the context of traditional school education and homeschooling. The hypothesis of the study was the assumption about the relationship between the level of psychological well-being and the form of education of elementary school children. In a study involving 60 schoolchildren aged 8-9 years (30 – in the homeschooling, 30 – in the school of education) and their parents, the Russian-language version of the “Scale of psychological well-being of children (PWB-c)” for children aged 8-9 years was used; the Dembo–Rubinstein self-esteem study method in the modification of A.V. Prikhozhan, a projective drawing “My family” and a survey of parents of primary school children on the author's questionnaire. The study showed no significant differences between the two groups on all scales of the PWB-c questionnaire. Satisfactory internal consistency of the questionnaire was shown (Cronbach's alpha=0.775). Data on the family drawing, the Dembo–Rubinstein method and the questionnaire for parents show that in families where children are taught at home, family relationships are perceived by children as more favorable and the level of claims of children is more adequate. Parents of children in family education are more focused on finding happiness for their child; parents of children in school are more focused on the academic success of their children. Authors showed prospects of further research of psychological well-being of elementary school children in the conditions of various forms of education. Ways to refine the PWB-c questionnaire and validate it are outlined.